2017
DOI: 10.5296/jas.v5i2.10762
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interactions on Cotton Fiber Traits and Their Implications on Variety Recommendation

Abstract: The objective of this study was to evaluate cotton fiber quality traits across diverse environments. This could lead to the selection of the best environment for cotton cultivations and the best adapted commercial cultivars. For this reason four main cotton regions were chosen as different environments: Thessaly, Thrace, Macedonia and Sterea Ellas. Five of the most commercial upland cotton cultivars (DP332, DP377, ST402, CELIA and ELSA) were used for evaluation of their fiber quality traits. Each cultivar was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…). Reflectance (Rd) and yellowness (+b) affected by both genotype and environment are two important factors that determine the fiber color grade in cotton [38]. The reflectance scale is between +40 (darker) and +85 (lighter/brighter) [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Reflectance (Rd) and yellowness (+b) affected by both genotype and environment are two important factors that determine the fiber color grade in cotton [38]. The reflectance scale is between +40 (darker) and +85 (lighter/brighter) [25].…”
Section: Resultsmentioning
confidence: 99%
“…The reflectance scale is between +40 (darker) and +85 (lighter/brighter) [25]. In studies from different regions, reflectance values changed from 72.28 to 74.50 in Southeastern Anatolia of Türkiye [38], and from 71.5 to 73.3 in Thrace, Macedonia, Central Greece and Thessaly of Greece [14]. Our results indicated that Rd values fluctuated from 69.62-71.0 (Great Meander and Bakırçay in 2020) to 73.74 (Söke in 2020)-73.82 (Bakırçay in 2019) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four main cotton-production Greek regions were selected as different environments (Greveniotis and Sioki, 2017), i.e. Thessaly, Sterea Ellas, Macedonia and Thrace.…”
Section: Methodsmentioning
confidence: 99%
“…Upland cotton (Gossypium hirsutum L.), is one of the main cultivations in Greece, with four main regions consisting a mega-environment (Baxevanos et al, 2006;2013;Greveniotis and Sioki, 2017). Improvement in fiber quality is the primary objective for cotton breeders, coping with the lack of reliable methods to measure fiber characteristics.…”
Section: Introductionmentioning
confidence: 99%